KEMANUSIAAN DALAM MEDIA: TELAAH ATAS GAYA JURNALISME MAJALAH TARBAWI DAN TEMPO - Edi Santoso (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2010)
One of effort to examine the claim of journalism practices is making a research about the news construction of the media.In this project, researcher aim to study journalism style of Tarbawi magazine—would by compared with Tempo, especially on coveringhumanity issues, by its news construction analyzed. The media contents were analyzed by using framing analysis of Entman model, sothe news construction of Tarbawi will appear. Journalism style of Tarbawi will be explicit by the opinion of Tarbawi editors that found byin depth interview. The result showed the news construction of Tarbawi on covering humanity issues tend to focused on personalproblem with more space for moral evaluation based on Islamic values. The contemplative and narrative writing of Tarbawi showed itsconscience journalism. The moral judgments always underlie Tarbawi coverage. This journalism style can be categorized asinterpretative journalism genre. This style and literary journalism is like-minded, especially for the narrative style of writing